2019
DOI: 10.3390/cancers11040526
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantification of Extranuclear ERα Using Phosphor-Integrated Dots for Predicting Endocrine Therapy Resistance in HR+/HER2− Breast Cancer

Abstract: In addition to genomic signaling, Estrogen receptor alpha (ERα) is associated with cell proliferation and survival through extranuclear signaling contributing to endocrine therapy (ET) resistance. However, the relationship between extranuclear ERα and ET resistance has not been extensively studied. We sought to measure extranuclear ERα expression by immunohistochemistry using phosphor-integrated dots (IHC-PIDs) and to assess its predictive value for ET resistance. After quantitative detection of ERα by IHC-PID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Guo et al. showed that a high ratio of extranuclear-to-nuclear estrogen receptor alpha (ERα) in patients with hormone receptor-positive and HER2-negative breast cancer indicates a decreased likelihood of benefiting from hormone therapy ( 30 ). Similar to our study, the PID score for PD-L1 expression showed a higher prognostic value than protein detection using IHC-DAB ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al. showed that a high ratio of extranuclear-to-nuclear estrogen receptor alpha (ERα) in patients with hormone receptor-positive and HER2-negative breast cancer indicates a decreased likelihood of benefiting from hormone therapy ( 30 ). Similar to our study, the PID score for PD-L1 expression showed a higher prognostic value than protein detection using IHC-DAB ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Welsh et al showed that the incidence of cytoplasmic ER staining only averaged 1.5% (ranging from 0–3.2%) in more over 3,000 breast carcinoma tissues although no information is available in the nuclear ER status of these cases [ 26 ]. On the other hand, Guo et al reported that high ratio of extranuclear-to-nuclear ER in ER-positive breast carcinoma was associated with poor overall survival and disease-free survival by immunohistochemistry using phosphor-integrated dots [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence signals of PIDs were observed using fluorescence microscopy (BX53; Olympus Corp., Tokyo, Japan) with a UPLSAPO 40 × 2 (Olympus) objective lens and charge-coupled device camera (DP73; Olympus) in five microscopic fields (with ~1000 cells investigated in each sample). The PID score (PIDs per cell) was thereafter determined ( Figure 1 ) [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory recently developed nanoparticles suitable for the quantitative immunohistochemical (IHC) method called phosphor-integrated dots (PIDs). Using PID-based IHC (IHC-PID), many biomarker proteins can be visualized and quantitatively analyzed at the single-particle level in paraffine-embedded, formalin-fixed tumor samples [ 13 , 14 ]. The IHC-PID method is a versatile optical technique that can accurately estimate protein expression independent of the optical system.…”
Section: Introductionmentioning
confidence: 99%